DIFFERENTIATION OF RUNNERS ATHLETES IN THE METABOLIC ADAPTATION TO THE BRUCE ERGOSPIROMETRY TEST: AN APPROACH BY DRIFTS IN RELATION TO THE STAGE OF TEST (Fiep Bulletin - online, 2013)
For the present study 34 runners (12 in 2008, 14 in 2009 and 8 in 2010) from the UNISC Athletics Team were evaluatedby anthropometry and ergospirometry associated with Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS)of whole blood for differentiation of blood adaptation patterns with regard to gender. The athletes underwent the Bruce ProtocolTreadmill Test, using gas analyzer and evaluating heart rate, maximum oxygen consumption (VO2max), maximum carbondioxide production (CO2max) and respiratory quotient (RQ) at rest (pretest ) and every 20 seconds up to 3 minutes after the endof the test (exhaustion or termination of the protocol). The evaluation of blood pressure was performed at rest, every 3 minprotocol (transition between stages) and after recovery. The blood collection by brachial venipuncture was performed in the pretestand 10 minutes after the termination of protocol (post test) and blood samples were analyzed by DRIFTS through the fullspectrum. For the male athletes, largest spectral differences were observed between the two stages in the years 2008 and 2010and the last one showed various regions with significant differences. For the female athletes, in the three years of collection thespectral ranges that showed significant differences were more numerous in 2010. This technique has proved to be sufficientlysensitive to the evaluation of adaptation of athletes during the Bruce Ergospirometry Test, besides being possible to observeparticularities regarding the different genders of athletes.
Keywords: athletes; DRIFTS; physical fitness